Kritik Ketimpangan Hukum Melalui Kisah Parasurama: Adaptasi Visual Prasi pada Meda Kaca dan Akrilik - Kadek Rifkyandi Septyan; I Wayan Sudiarta; I Nyoman Rediasa (Universitas Pendidikan Ganesha, 2026)
The discrepancy in law enforcement in Indonesia sometimes leads to phenomena of injustice that contradict the principle of equality before the law. This phenomenon of abuse of authority and corruption practices incites public anger, demanding the employment of art as a means of critical expression. This study aims to explore the visual adaptation techniques of Prasi art on contemporary media such as glass and acrylic, as well as to visualize socio-political critique through the legendary figure Parasurama Avatara. The method used is the Design and Development approach, which included stages for planning, technical experiment, and work evaluation stages. The creation process is carried out using engraving techniques with a fine drill on transparent media while maintaining the visual character of Balinese wayang. The results and discussion show that this adaptation produced four main works: “Disparitas,” which represents the disparity of legal transparency, “Parasurama vs Kartawirya Arjuna” and “Parasurama vs Everybody” as symbols of firmness against arbitrariness, and “Expectation,” which conveys as message of harmony through the Tri Hita Karana philosophy. The conclusion of this research suggest that the use of glass and acrylic media symbolically strengthens the message of legal transparency and firmness. This adaptation validates that the traditional art of Prasi is capable of contextualizing contemporary social issues while maintaining its visual identity. Keywords: Prasi, Parasurama, Glass and Acrylic, Discrepancy in Law, Engraving.